Reproductive Implications and Management of Congenital Uterine Anomalies: Scientific Impact Paper No. 62 November 2019. (20th November 2019) - Akhtar, MA; Saravelos, SH; Li, TC; Jayaprakasan, K; ,
Plain language summary: Congenital uterine anomalies (CUAs) are malformations of the womb that develop during fetal life. When a baby girl is in her mother's womb, her womb develops as two separate halves from two tubular structures called 'müllerian ducts', which fuse together before she is born. Abnormalities that occur during the baby's development can be variable from complete absence of a womb through to more subtle anomalies, which are classified into specific categories. While conventional ultrasound is good in screening for CUAs, 3D ultrasound is used to confirm a diagnosis. If a complex womb abnormality is suspected, MRI scanning may also be used, with a combination of laparoscopy in which a camera is inserted into the cavity of the abdomen, and hysteroscopy, when the camera is placed in the womb cavity. As there can be a link between CUAs and abnormalities of the kidney and bladder, scans of these organs are also usually requested. Although CUAs are present at birth, adult women typically do not have any symptoms, although some may experience painful periods. Most cases of CUA do not cause a woman to have difficulty in becoming pregnant and the outcome of pregnancy is good. However, these womb anomalies are often discovered during investigations for infertility or miscarriage. Moreover, depending upon the type and severity of CUA, there may be increased risk of first and second trimester miscarriages, preterm birth, poor growth of the baby in the mother's womb (fetal growth restriction), pre‐eclampsia and difficult positioning of the baby for birth (fetal malpresentation). Surgical treatment is only recommended to a woman who has had recurrent miscarriages and has a septate uterus, i.e., the womb cavity is divided by a partition. In this case, surgery may improve her chances for a successful pregnancy, although the risks of surgery, especially scarring of the womb should be considered. However, further evidence from randomised controlled trials are required to provide conclusive evidence‐based recommendations for surgical treatment for septate uterus. Surgical treatment for other types of CUAs is not usually recommended as the risks outweigh potential benefits, and evidence for any benefits is lacking. Women with CUAs may be at an increased risk of preterm birth even after surgical treatment for a septate uterus. These women, if suspected to be at an increased risk of preterm birth based on the severity of CUA, should be followed up using an appropriate protocol for preterm birth as outlined in UK Preterm Birth Clinical Network Guidance. 1 >